A critical discourse analysis of the coverage of operation "Restore Order" (Operation Murambatsvina) by Zimbabwe's weekly newspapers, the state-owned The Sunday Mail and the privately owned The Standard, in the period 18 May to 30 June 2005,A critical discourse analysis of the coverage of 'Operation Restore Order' by Zimbabwe's newspapers; the Sunday Mail and the Standard, in the period 18 May to 30 June 2005 - Mukundu, Rashweat (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
On May 16 2006 the government of Zimbabwe embarked on a clean-up programme of urban centres, destroying informal human settlements and informal businesses. This operation, which the government called operation "Restore Order", resulted in the displacement of nearly one million people and left thousands of families homeless. This study is a discussion and an analysis of the coverage of the clean-up operation by two of Zimbabwe's leading Sunday newspapers, The Sunday Mail and The Standard. The Sunday Mail is owned by the Zimbabwe government and The Standard is privately owned and perceived to be oppositional to the current Zimbabwe government. The two newspapers, therefore, covered the clean-up operation from different perspectives and often presented conflicting reports explaining why the clean-up operation was carried out and the extent of its impact on the lives of millions of Zimbabweans. The chosen research approach is the Critical Discourse Analysis (CDA) framework as developed by Fairclough (1995). Using CDA, this study seeks to find out and expose the underlying ideological struggles for hegemony between different social and political groups in Zimbabwe and how the newspapers became actors in this process. This process is made possible by looking at how news reporting is organised in the two newspapers, issues of language use, sourcing and external factors that influenced the coverage of the operation.
Keywords: Operation Murambatsvina, Zimbabwe, 2005-; Political persecution -- Zimbabwe; Mass media -- Political aspects -- Zimbabwe; Press and politics -- Zimbabwe; Freedom of the press -- Zimbabwe; Newspapers -- Objectivity -- Zimbabwe; Journalistic ethics -- Zimbabwe; Critical discourse analysis; Sunday Mail (Zimbabwe); The Standard (Zimbabwe)